Gallant - Schwab, Victoria (Greenwillow Books, 2022)
Olivia Prior has grown up at the grim Merilance School for Girls with no no past except for her one treasure, her mother's journal, so when a letter arrives inviting her to come home to ruinous manor, Gallant, she seizes the chance to find out about her family.